Characterization of physical and mineralogical properties of anthracite and bituminous coal tailings. Issue 9 (2nd September 2021) - Liew, Min; Xiao, Ming; Liu, Shimin
ABSTRACT: In this paper, the physical and mineralogical properties of two types of tailings produced from anthracite and bituminous coals were studied and compared. The following characteristics were determined: absolute density, particle size, and elemental and mineral compositions. The goal of this research is to provide basic characterizations of the two common coal tailings for potential future coal tailings reprocessing and combustion. Anthracite tailings (i.e., tailings from the higher rank coal) are characterized to have higher absolute densities, coarser grain size distributions, higher hydrophobicity, and less platy particles, compared to bituminous coal tailings. The uniformities of grain size are similar for both coal tailings. Based on these properties, analyses show that coal fines are easier to be extracted or separated from anthracite tailings. The average particle size of both coal tailings, however, may need to be modified accordingly to meet the specifications of available combustion techniques.